Uterine angioleiomyoma in an African green monkey (Chlorocebus aethiops sabaeus). Issue 1 (8th November 2016) - Valentine, Matthew John; Beierschmitt, Amy; DeLay, Josepha; Callanan, John Joseph
Abstract: Background: A uterine neoplasm was observed, as an incidental finding, during post‐mortem examination of a 26‐year‐old female multiparous African green monkey ( Chlorocebus aethiops sabaeus ). The intramural, expansile, 2 to 3 cm well‐demarcated, dark‐red, nodular neoplasm was located on the anterior uterine body (corpus) wall. Methods: The mass was examined by light microscopy and by immunohistochemistry. Results: The mass was confirmed as a cavernous uterine angioleiomyoma (syn. vascular leiomyoma) characterized by abundant intratumoural vasculature lined by Factor VIII‐positive endothelial cells and surrounded by smooth muscle actin‐positive cell proliferations. Conclusion: Angioleiomyoma sharing the characteristics of intramural human cavernous uterine angioleiomyoma should be considered in the differential diagnosis of uterine tumours in non‐human primates.